A Reversible Conversion Reaction of Metal and BF4− Anions for the Use in Li-Ion Batteries. Issue 5 (30th January 2016) - Matsui, Tooru; Nakata, Akiyoshi; Hirai, Toshiro; Yamaki, Jun-ichi; Ogumi, Zempachi
Abstract : It was found that Fe wire can be electrochemically oxidized to a white powder in a LiBF4 /THF electrolyte (LiBF4 : THF = 1: 10 (molar ratio)). The counter electrode was Li metal, and the white powder was identified as Fe(BF4 )2 6THF, by ion chromatography, ICP-AES, and TG-GC/MS. Therefore, the electrochemical reaction occurring was Fe(BF4 )2 6THF + 2e − ⇌ Fe + 2BF4 − + 6THF. From cyclic voltammetry analysis, the oxidation and reduction potentials were 2.9 V and 2.4 V vs. Li/Li + . This reaction is very similar to the conversion reaction of a Li-ion cell. It is well known that M-X compounds (where M is a metal) with X = O, N, F, Cl, S, or P are active materials for the conversion reaction. From our experiment, FeBF4 is also an active material for the conversion reaction, where X is BF4 . The theoretical energy density of a cell for the reaction of Fe(BF4 )2 6THF (2.6 V) is 206 Wh/kg, which is small compared to the theoretical energy density of Li0.5 CoO2 cell (575 Wh/kg). However, if an electrolyte that produce Fe(BF4 )2 without 6THF can be found, the theoretical energy density would be 573 Wh/kg.